2020
DOI: 10.1016/j.scog.2019.100167
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia, recovery and the self: An introduction to the special issue on metacognition

Abstract: In this special issue, work is presented linking metacognition among persons with schizophrenia with a range of psychosocial outcomes including vocational functioning, empathy, motivation, self-evaluation, and other cognitive functions. This overview will highlight how these works allow for the quantitative study of processes which underpin alterations in self-experience in schizophrenia, which in turn allows self-experience to be studied as part of a larger set of brain-based and social phenomena whose intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Within a similar conception, Narrative therapies have reported good clinical outcomes among severe mental illness (Vromans & Schweitzer, 2011;Newberg, 2016). Also, psychotherapies based on metacognitive approach, which are focused on patients self-experiences and making them sense of the challenges through dialogue (Lysaker et al, 2020), have demonstrated the development of a sense of personal agency, a greater capacity to tolerate and manage painful affects and emotion (Jong et al, 2017) and a increasing sense of psychosocial challenges (Hasson-Ohayon et al, 2017). Hence, it is widely accepted the importance of facilitating the re-emergence of internal dialogue through external dialogue.…”
Section: Discussionmentioning
confidence: 99%
“…Within a similar conception, Narrative therapies have reported good clinical outcomes among severe mental illness (Vromans & Schweitzer, 2011;Newberg, 2016). Also, psychotherapies based on metacognitive approach, which are focused on patients self-experiences and making them sense of the challenges through dialogue (Lysaker et al, 2020), have demonstrated the development of a sense of personal agency, a greater capacity to tolerate and manage painful affects and emotion (Jong et al, 2017) and a increasing sense of psychosocial challenges (Hasson-Ohayon et al, 2017). Hence, it is widely accepted the importance of facilitating the re-emergence of internal dialogue through external dialogue.…”
Section: Discussionmentioning
confidence: 99%
“…It is currently not clear what factors contributed to the slow rate of AHs reductions observed in the Sheng et al study. However, schizophrenia is associated with reductions in selfawareness, introspection and metacognitive abilities (Cella et al, 2019;Lysaker et al, 2019;Silberstein and Harvey, 2019). These deficits may have contributed to the slow rate of improvement when meditation only was used as a therapeutic approach.…”
Section: Limitationsmentioning
confidence: 99%
“…Both involve specific and subtle dysfunctions that affect perception, thought, and mood, but which stem from atypical inference about-and faulty control over-one's higher-order states and processes. These are of higher order in that they govern the attribution of confidence to one's own perceptions (Lysaker et al, 2020;Palmer et al, 2017).…”
Section: Towards a Scientific Study Of Metacognitionmentioning
confidence: 99%